Effects of different doses of dexmedetomidine combined with sufentanil in intravenous controlled analgesia after Salter osteotomy in children - He, Zhiwei; Ni, Huanhuan; Wang, Wei (Frontiers in Pediatrics, 2024)
Background: This study aimed to investigate the effect of different dose of dexmedetomidine combined with sufentanil on postoperative analgesia in developmental hip dislocation in children after Salter osteotomy.The clinical data of 98 children with developmental hip dislocation were selected, who underwent Salter osteotomy in our center between January 2020 and February 2023. The children were randomly divided into four groups according to the application of patient controlled intravenous analgesia (sufentanil+granisetron±dexmedetomidine). All children received sufentanil 1 μ g/kg/d and granisetron 3 mg, and Group A no dexmedetomidine, Group B 0.5 μ g /kg/d, Group C 0.75μg /kg/d, Group D 1.0μg /kg/d dexmedetomidine. The pain indicators and immune factor levels of children in each group were compared.The heart rate(HR) and respiratory rate(RR) at 2h after operation in group C and D were significantly lower than those of group A and group B (P<0.05). Pain scores decreased over time after treatment in all groups. When compared at the same time point, children in Group D had the lowest pain scores, which were significantly lower than the other three groups (P<0.05). The total consumption of sufentanil in group C and D was significantly lower than that in group A (P<0.05).On 1st day after surgery, the children in Group D had lower levels of serum Adrenocorticotropic hormone(ACTH), Interleukin-6(IL-6), and Corticosterone(COR) levels than those in Group A (P<0.05).1.0μ g /kg/d dexmedetomidine combined with sufentanil in intravenous controlled analgesia after Salter osteotomy for developmental hip dislocation in children has better analgesic effect, less consumption of sufentanil, and low incidence of opioid adverse reactions.